Ruptured diaphragmatic hernia with grade I splenic injury: A case report. (September 2022) - Shakya, Yagya Laxmi; Allam, Parbej; Silwal, Aarjabi; Acharya, Sajana; K.C., Shradha; Pant, Samriddha Raj
Abstract: Introduction and importance: Traumatic diaphragmatic injury (TDI), although rare, is associated with high mortality and morbidity and timely recognition is important. Case presentation: We present a case of a 44-year-old male who fell from a three-story building and presented with complaints of shortness of breath and chest pain. On examination, his chest compression test and extended focused assessment with sonography in trauma (E-FAST) were positive. Chest X-ray showed loss of diaphragmatic contour, fracture of fifth to eleventh ribs on the left side, and opacities in the left hemithorax. Contrast-enhanced computed tomography of chest, abdomen, and pelvis showed bowel loops over the left hemithorax with grade 1 splenic injury. A diagnosis of ruptured diaphragmatic hernia with grade I splenic injury was made and emergency primary repair of the diaphragm was done via thoracotomy. Discussion: Clinical diagnosis of TDI is difficult and can be misdiagnosed as a pneumothorax. In addition, the subtle presentation can often be missed. CT scan of the chest and abdomen is the imaging of choice to reach a diagnosis. Once diagnosed, emergency surgery via laparotomy or thoracotomy is mandatory. Delay in diagnosis can have a fatal consequence or delayed complications which have high mortality. Conclusion: Diaphragmatic injury should be suspected in all blunt thoracoabdominal traumas, and the presence of this injury should be excluded to prevent late complications. Timely intervention can provide excellent outcomes. Highlights: Diaphragmatic rupture should be considered among traumatic patients with shortness of breath. Delay in diagnosis and treatment have high morbidity and mortality. Timely intervention can provide excellent outcomes.